Would the width of a metal rib spreader affect postoperative pain in patients who undergo video-assisted mini-thoracotomy (VAMT)? - Wang, Linlin; Ge, Lihui; Fu, Ninghua; Ren, Yi (Frontiers in Oncology, 2022)
Background Hitherto, no study has evaluated postoperative pain in patients with non-small cell lung cancer (NSCLC) treated with video-assisted mini-thoracotomy (VAMT). In this study, we aimed to assess postoperative pain related to the width of the metal rib spreader in patients who underwent lobectomy using VAMT. Methods We retrospectively analysed the data of 94 consecutive patients with NSCLC who underwent lobectomy using VAMT at our institution between March 2019 and May 2022. We divided the patients into groups according to the width ratio of the rib spreader to that of a single intercostal space. Patients with width ratios ≤ 2.5 times were assigned to group A, and those with width ratios > 2.5 times were assigned to group B. Pre-, intra-, and postoperative data were collected and reviewed. Results We successfully performed VAMT in 94 patients with NSCLC. Forty-five patients were in group A, and 49 were in group B. There were no intraoperative mortalities, although one patient, due to respiratory failure, experienced 30-day mortality. There were no significant differences between the two groups in terms of the blood loss volume, operative time, drainage time, postoperative complications, length of hospital stay, or number of lymph node stations explored and retrieved. The drainage volumes (Day 1–Day 3) were higher in group B than in group A (P < 0.05). The postoperative visual analogue scale (VAS) pain scores were significantly lower in Group A than in Group B at 12, 24, and 48 h (P < 0.05), although there was no significant difference in the VAS scores between the two groups at 72 h and 1 week postoperatively (P > 0.05). Conclusion The smaller the width of the metal rib spreader used in surgery, the less pain experienced by the patient and the faster the recovery. Multicentre, randomised, controlled trials should be conducted in the future.